METHODS OF TEACHING SPEAKING TO YOUNG LEARNERS. - Xaydarova Nigora; Umarova Nigora (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation: This article highlights the effective strategies such as role - play, brainstorming,  picture  narrating  and  playing  cards  to  turn  speaking  into  more engaging part of a learning process. It emphasizes thematic teaching, group work and interactive activities to enhance speaking abilities and create friendly and engaging learning environment.